HEALTH PROMOTION: PERCEPTIONS OF STUDENTS OF COURSE GRADUATION IN NURSING - Carine Vendruscolo; Letícia de Lima Trindade; Édlamar Kátia Adamy; Alyne Mendes Correia (Universidade Federal de Santa Maria, 2014)
http://dx.doi.org/10.5902/217976929171 Aim: to meet the perception of students of the final stages of the undergraduate curse in nursing on the Promotion of Health (PS). Method: descriptive study, conducted whit interviews, treated using Content Analysis, taking into reference to the contemporary concept of PS, which suggests the of individual efforts and collective action to intervene in the quality of life of the population. Results: emerged as categories: PS Concept; Sources of knowledge of the students on the PS and spaces in which PS occurs. The student´s idea suggests the influence of the Ottawa Charter, the presence of the university as a source of knowledge and remnants of a design centered on outdated concepts of PS. Final considerations: the university needs to invest in training, with the theme as cross in the educational processes, taking into account the movements of reorientation training in health.